Miejsce agrobiznesu i agroturystyki w strategiach rozwoju dolnośląskich jednostek samorządowych - Bąk, Dominika; Bodak, Andrzej (Agribusiness and Agrituristic in Strategies of Lower Silesian Self Government Units Development, 2005)
In this paper there is presented a range of strategic planning in communities' self governments development. Research carried out in Lower Silesian communities indicates that administration authorities only in small degree support the modernization of agribusiness by realizing strategy of units.The main directors of strategic activities in the south of the region are connected with the development of the agroturistic. It is in accordance with the idea of multi-purpose development of rural areas. It has also been proved, that basic ways of the expansion strongly depend on the specific characteristic of a region.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 50-54